Fabrication and modulation of flexible electromagnetic metamaterials - Yanshuo Feng; Misheng Liang; Xiaoguang Zhao; Rui You (Microsystems & Nanoengineering)
Abstract Flexible electromagnetic metamaterials are a potential candidate for the ideal material for electromagnetic control due to their unique physical properties and structure. Flexible electromagnetic metamaterials can be designed to exhibit specific responses to electromagnetic waves within a particular frequency range. Research shows that flexible electromagnetic metamaterials exhibit significant electromagnetic control characteristics in microwave, terahertz, infrared and other frequency bands. It has a wide range of applications in the fields of electromagnetic wave absorption and stealth, antennas and microwave devices, communication information and other fields. In this review, the currently popular fabrication methods of flexible electromagnetic metamaterials are first summarized, highlighting the electromagnetic modulation capability in different frequency bands. Then, the applications of flexible electromagnetic metamaterials in four aspects, namely electromagnetic stealth, temperature modulation, electromagnetic shielding, and wearable sensors, are elaborated and summarized in detail. In addition, this review also discusses the shortcomings and limitations of flexible electromagnetic metamaterials for electromagnetic control. Finally, the conclusion and perspective of the electromagnetic properties of flexible electromagnetic metamaterials are presented.